Pengaruh Konsentrasi Zat Pengatur Tumbuh dan Bagian Asal Bibit Terhadap Pertumbuhan Vegetatif Pembibitan Tebu - Wardani, Oki Puspita; Priyadi, Priyadi; Yatmin, Yatmin (Politeknik Negeri Lampung, 2021)
Increasing sugarcane productivity can be done by providing good quality seedlings. The research objective was to study plant growth regulator concentration and part of seedling origin in sugarcane seedlings. This study was conducted on Pujodadi Village, Trimurjo, Central Lampung from September to December 2020. The study used a factorial randomized block design with two factors and three replications. The first factor is concentration of plant growth regulator which consists of 5 levels: Z0 (0 ml.l-1), Z1 (3.5 ml.l-1), Z2 (7 ml.l-1), Z3 (10.5 ml.l-1) and Z4 (14 ml.l-1). The second factor is the origin of the seedling consists of three parts: P1 (upper stem), P2 (middle stem), and P3 (bottom stem). The results showed that the plant growth regulator concentration significantly increased the percentage of growth and 50% of the seedlings sprouted. The seedling origin of the upper stem showed the best growth compared to the middle and bottom stem. There was no interaction between plant growth regulator concentration and the part of seedling origin on sugarcane vegetative growth.